An empirical study on the relationship between board size, audit committee characteristics and financial performance: evidence from licensed commercial banks in sri lanka - Silva, O.D.; Hewage, Y.M. (University of Jaffna, 2022)
Purpose: The purpose of this study is to investigate the relationship between board size (BS) and audit committee (AC) characteristics, namely AC size, AC meeting frequency, and AC expertise which can be treated as integral components of CG on the FP using the evidence of Licensed Commercial Banks (LCB) in Sri Lanka. Methodology: The study was carried out using secondary data obtained through published annual reports of 24 LCB, including 96 observations in the Colombo Stock Exchange (CSE) from 2016 to 2019.Financial performance was measured by Return on Assets (ROA) and Return on Equity (ROE) using two multiple regression models upon satisfying the pre-diagnosis tests. Findings: The findings demonstrated BS has a significant negative relationship with FP measured by both ROA and ROE. Further, AC expertise depicted a significant positive relationship with FP measured by ROE while insignificantly related with ROA. However, the other remaining characteristics did not significantly influence on FP. Research limitations: This study has been conducted on financial firms in Sri Lanka which implies that the generated findings may not be transferrable to non- financial firms. Hence, it would be better to consider different countries, small, medium and large-scale enterprises and private and public undertakings to make findings generalizable to all types of firms. Also, the current study only stresses on key CG elements such as board size along with key AC characteristics. Future studies should consider more independent variables including board diversity, tenure of AC, independence of the AC which may significantly influence on FP. Implications: Overall, this analysis highlights the importance of CG mechanisms which may be useful for policymakers for future designs. Further, the findings of the study would be helpful for management to make appropriate decisions regarding optimizing the board size and AC characteristics in order to safeguard the interests and demands of the different stakeholders of the firms.
Keywords: Board size; Audit committee; Audit committee characteristics; Firm performance; Licensed commercial banks in Sri Lanka